2002
DOI: 10.1177/014556130208100819
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Lipoblastoma of the Parapharyngeal Space

Abstract: Lipoblastoma is a rare benign tum or that occ urs primarily in children yo unge r than 3 yea rs of age. Fewer than 100 cases have been reported in the literature, and only eight cases have been previously reported in the head and nec k; two of them occ urred in the parotid region, where the different ial diagnosis beco mes quite extensive. We repo rt a new case of head and neck lipo blastomaone that occ urred in the parapharyngeal space, a site that has not been previously reported. By doing so, we hope to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
10
0
3
Order By: Relevance
“…The study of 24 patients by Dilley et al [8] supports our data showing no clear majority of lesions in the extremities. Other reported locations include chest wall [2], mediastinum [10], heart [11], lung [12], retroperitoneum [9], omentum [13], mesentery [14], scrotum [15,16], inguinal canal [8], perirectal area, back [17], axilla [3], forehead [18], parotid gland, parapharyngeal space [19], and eyelid [20]. We add to this list of sites lip and labia majora.…”
Section: Discussionmentioning
confidence: 99%
“…The study of 24 patients by Dilley et al [8] supports our data showing no clear majority of lesions in the extremities. Other reported locations include chest wall [2], mediastinum [10], heart [11], lung [12], retroperitoneum [9], omentum [13], mesentery [14], scrotum [15,16], inguinal canal [8], perirectal area, back [17], axilla [3], forehead [18], parotid gland, parapharyngeal space [19], and eyelid [20]. We add to this list of sites lip and labia majora.…”
Section: Discussionmentioning
confidence: 99%
“…10 Farrugia et al reported another case of lipoblastoma in the neck which had presented with rapidly enlarging mass, mimicking cystic hygroma. 11 A case of lipoblastoma in parapharyngeal space was reported by DePasquale et al 12 On imaging, lipoblastoma appears as a well-defined soft tissue mass, often with lobular appearance and having internal septations. The imaging appearance of lipoblastoma depends on the proportion of fat relative to the amount of myxocollagenous stroma.…”
Section: Discussionmentioning
confidence: 99%
“…22 Myxoid stroma and lipoblasts will exhibit high intensity on T2weighted images. 23 Therefore, despite the usefulness of MRI in assessment of lipoblastoma, it is not diagnostic, due to the presence of similar findings in other benign and malignant fatty tumors. Histologic analysis, therefore, is still mandatory.…”
Section: Discussionmentioning
confidence: 99%